Studi Dampak Poison Control Centre di Beberapa Negara dan Potensi Penerapannya di Indonesia - Aisyah Safira Mulia; Raden Bayu Indradi; Fairuz Murti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
According to PUSAKOM in 2022, the prevalence of poisoning in Indonesia in 2021 was 5,921 cases, which is the total number of cases from various categories of causes of poisoning. It was found that 998 cases (17%) were cases of drug and food poisoning, and the other 4,923 cases (83%) were not cases of drug and food poisoning. Poisoning is a condition where psychoactive substances enter which cause disturbances in consciousness, cognition, perception, effects, behavior, function and psychophysiological responses. The Poison Control Center (PCC) was established to assist in the prevention, diagnosis and management of toxicity cases. PCC contributes to various sectors, including education in the field of toxicology and public education, public health by reducing the number of poisoning cases, to the economy by producing a high cost-benefit ratio. However, PCC has not yet been formed in Indonesia. Therefore, there is a need to study the impact of the Poison Control Center and its potential when implemented in Indonesia. The analysis was carried out using article and literature review methods. The results obtained from the review show that the Poison Control Center has enormous potential when implemented in Indonesia from an economic, educational, and health perspective.